Reducing prejudice and stereotyping in schools - Stephan, Walter G.; Banks, James A. (New York : Teachers College Press, 1999)
Despite all the laws and social programs designed to increase racial equality, there are still major problems between racial, ethnic, and cultural groups in the United States. This book was written to assist educators in designing and implementing classroom interventions that will help students to develop more positive racial and ethnic attitudes and behaviors. The author provides an up-to-date review of the theories of prejudice and stereotyping; a careful examination of the conditions under which changes in prejudice and stereotypes can be accomplished; a wide array of techniques for improving race relations in schools; and specific recommendations to help educators select the programs that are most suitable for the schools in which they teach.
Recommendations for intergroup relations programs
Keywords: predrasude; stereotipi; škola; odnosi među grupama